Traumatic Brains and Broken Hearts: Mending the Donor Shortage in Cardiac Transplantation - Thomas, Sunu S.; D’Alessandro, David A. (Journal of the American College of Cardiology, 2017)
[...]tremendous attention has been paid to finding ways to expand the donor pool. Cardiac investigations, including coronary angiography and right-sided heart catheterization, are motivated by specific transplantation center practices and often the obligate vetting of a donor already provisionally accepted for a recipient pending serial testing. [...]the opportunity for further evaluation of a marginal donor is influenced by the donor family’s willingness, resource availability for study equipment and expert personnel, and even competing surgical timetables involving the procurement of noncardiac organs from the same donor. Heart transplantation will remain the gold standard for end-stage heart disease for the foreseeable future. Because the overall numbers are quite small, well-designed retrospective analyses remain important for the assessment of current practices and to use a scarce but invaluable resource most efficiently and effectively.